2007
DOI: 10.1016/j.vetmic.2006.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of a SAT-1 outbreak of foot-and-mouth disease in captive African buffalo (Syncerus caffer): Clinical symptoms, genetic characterisation and phylogenetic comparison of outbreak isolates

Abstract: African buffalo (Syncerus caffer) play an important role in the maintenance of the SAT types of foot-and-mouth disease (FMD) in southern Africa. These long-term carriers mostly become sub-clinically infected, maintaining the disease and posing a threat to other susceptible wildlife and domestic species. During an unrelated bovine tuberculosis experiment using captive buffalo in the Kruger National Park (KNP), an outbreak of SAT-1 occurred and was further investigated. The clinical signs were recorded and all a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…There are unequivocal cases of extensive vesicles and debilitating FMD in buffalo (44,45). The reasons for these discrepancies in disease severity are unclear, and the occurrence of vesicles may depend on the interplay between virus, host, and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…There are unequivocal cases of extensive vesicles and debilitating FMD in buffalo (44,45). The reasons for these discrepancies in disease severity are unclear, and the occurrence of vesicles may depend on the interplay between virus, host, and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…3) over 4 months, which is rapid compared to two previous studies of genetic change in buffaloes. Vosloo et al (1996) showed a substitution rate of 1.64 % per year over a similar genetic region for a SAT-2 virus in carrier buffaloes and Vosloo et al (2007) estimated a rate of 1.1 % per year in an outbreak of SAT-1 in buffalo that also led to the establishment of a carrier state. It is not known whether FMDV might evolve faster in cattle than buffaloes, or whether the faster rate of change observed in this study might have arisen as a result of vaccine induced selection pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Antigenic variants can be selected for in immune or partially immune hosts (Gebauer, De la Torre, Gomes, Maten, Barahona, Tiraboshi, Bergman, De Mello & Domingo 1988), although Diez, Mateu & Domingo (1989) reported that antigenic variants may accumulate over time even in the absence of antibody selection. Studies have shown that cattle and buffalo carriers (subclinically infected animals) may be a significant source of genetic variation (Salt, Samuel & Kitching 1996;Vosloo, Bastos, Kirkbride, Esterhuysen, Janse van Rensburg, Bengis, Keet & Thomson 1996;Vosloo, De Klerk, Boshoff, Botha, Dwarka, Keet & Haydon 2007). In particular, capsid protein VP1, encoded by the 1D gene, greatly contributes to the antigenicity of FMDV Mateu, Camarero, Giralt, Andreu & Domingo 1995) due to the existence of an immuno-dominant site, located between beta-strands G and H (the G-H loop) of VP1 which also acts as the cell receptor recognition site (Kitson, McCahon & Belsham 1990).…”
mentioning
confidence: 99%
“…Buffalo calves play an important role in the dynamics of the disease, because they are the most infectious individuals (Gainaru et al, 1986). They become susceptible to FMD in the period after their maternal antibodies wane and before their natural immunity develop, which coincides with the age three to eight months (Bastos et al, 2000;Vosloo et al, 2007). The maintenance of FMD by wildlife makes the eradication of the virus impossible without the destruction of large numbers of African buffaloes -a solution that is both ecologically and morally untenable (Thomson et al, 2003a).…”
Section: Transmission Cycle Of Foot-and-mouth Disease In South Africamentioning
confidence: 99%